2012
DOI: 10.1155/2012/247352
|View full text |Cite
|
Sign up to set email alerts
|

170 Years of “Lock-and-Key”: Genital Morphology and Reproductive Isolation

Abstract: The divergent genital morphology observed among closely related animal species has long been posited as a mechanism of reproductive isolation. Despite the intuitive appeal that rapidly evolving genitalia might cause speciation, evidence for its importance—or even its potential—in reproductive isolation is mixed. Most tests of genital structural isolation between species often fail to find convincing evidence that differences in morphology prevent copulation or insemination between species. However, recent work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(176 citation statements)
references
References 42 publications
7
169
0
Order By: Relevance
“…First, crossings between species with different genital sizes are almost always impossible or lethal to females, especially when males are much larger (Masly 2012). Second, when size dimorphism is marked, selection can operate to match genital size.…”
Section: For Mechanically Feasible Copulationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, crossings between species with different genital sizes are almost always impossible or lethal to females, especially when males are much larger (Masly 2012). Second, when size dimorphism is marked, selection can operate to match genital size.…”
Section: For Mechanically Feasible Copulationmentioning
confidence: 99%
“…They conclude that although there is no evidence that lock and key explains most instances of genital elaboration in insects, the hypothesis has not really been falsified. A more recent review centers on examining hybridization between species, in which genital morphology seems to play a role in reproductive isolation via mechanical incompatibility (Masly 2012). Lock and key is supported by recent studies of millipede genitalia (e.g., Tanabe and Sota 2008;Simmons 2012, 2013).…”
Section: For a Lock-and-key Mechanism To Prevent Hybridizationmentioning
confidence: 99%
“…santomea is endemic to the small African volcanic island of São Tomé, while D. yakuba is widely distributed in central Africa (Lachaise et al 2000;Markow and O'Grady 2006). These two species form a hybrid zone in São Tomé (Lachaise et al 2000;Llopart et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in polyandric systems, female choice can promote male genitalic diversification (Arnqvist 1998), although the modus operandi is still disputed (Hosken and Stockley 2004). Furthermore, structures involved in mating are generally species-specific (which is the case in Scissicauda ) and evolve fast (Eberhard 2004), often as a consequence of sexual selection (Hosken and Stockley 2004), and may promote reproductive isolation either by structural or sensory lock-and-key, thus avoiding hybridization (Masly 2012). Future field observations and detailed histological studies would be useful to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%